Application of biochar and fate of soil nutrients - Khan, KT; Chowdhury, MTA; Huq, SM Imamul (Bangladesh Journal of Scientific Research, 2016)
An in vitro incubation study was conducted with soil having seven applications of different treatments of biomass and biochar including a control. The biochar and biomass were applied at a rate of 5 t/h a and incubated at field moisture condition for 30, 60 and 90 days individually in different pots. Total organic carbon (C), total nitrogen, phytoavailable nitrogen (N), phosphorus (P), sulfur (S) and potassium (K) were determined at the end of each incubation period. Total soil organic carbon (SOC), showed a substantial declining trend in all the soils - more prominent in the biochar treated soils than its corresponding biomass treated soils. The pH, total N, phytoavailable N, P, K were substantially higher in the biochar treated soils irrespective of the incubation days compared to the biomass treated soils. Conversely, the available S contents of the biochar treated soils were lower than that of biomass treated soils. The effect of biochar on these nutrients vis-à-vis soil health is discussed. Bangladesh J. Sci. Res. 27(1): 11-25, June-2014